“Cut-Off” Effect of Antioxidants And/Or Probes of Variable Lipophilicity in Microheterogeneous Media - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C (Elsevier Ltd, 2016)
The activities of two hydrophilic (ascorbic acid and Trolox) and two hydrophobic (α-tocopherol and BHT) antioxidants were measured by reaction with a series of 4-alkanoyloxyTEMPO radical probes 1 in buffered (pH 7), aqueous, micellar solutions of reduced Triton-X 100. In all cases, a cut-off effect was observed, in line with previous observations of the same effect for the partitioning of probe series 1 in this medium. These results support an interpretation of the cut-off effect in food emulsions, based on the “amphiphobic” nature of either the antioxidants or probes: competition between two molecular moieties, for the micellar hydrophobic core, tends to expose a reacting fragment differently to a more hydrophilic microenvironment, as the probe or antioxidant hydrophobicity increases. © 2016 Elsevier Ltd